The Third Mission in the Academic Profession: Empirical Insights into Academic Identities - Vitus Püttmann; Stephan L. Thomsen (Institute of Labor Economics (IZA), 2022)
In line with the growing relevance of higher education and science for societal development and innovation processes, there has been a steady increase in the salience of interrelations with the extra-academic environment in the context of academics' work. Insights into the status of this so-called third mission in the academic profession remain fragmented, however. We use the concept of an academic identity as an analytical lens to investigate this status empirically based on an original survey among 4,284 professors in Germany across the full range of academic disciplines. The results show that the third mission is firmly included in the academic identities of many, but not all, professors and that the forms of inclusion differ. Specifically, we are able to identify four types of identities: (1) the dedicated type who embraces the third mission as a whole; (2) the idealistic type who emphasizes responsibility toward society and sociopolitical matters; (3) the pragmatic type who emphasizes material work-related and personal benefits; and (4) the reserved type, characterized by an overall distanced stance. We furthermore find evidence of a strong impact of disciplinary communities on the specific types of identities that academics develop, whereas the organizational context and the cohorts to which academics belong appear less relevant. In addition, there are indications that individual characteristics shape the identity formation process. Last, there are strong and differential associations between academics' identities and their actual third mission engagement. Overall, it appears that the third mission—at least if its multifaceted nature is considered—is a relevant area of activity for a significant share of the academic profession.
Keywords: I23; O35; O36; 330; third mission; knowledge transfer; continuing education; societal engagement; academic profession; academic identity; professor